Israel and Palestine: some critical international relations perspectives on the 'two-state' solution - Pienaar, Ashwin Mark (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2010)
This research questions whether Israel and Palestine should be divided into two states. Viewed through the International Relations (IR) theories of Realism and Liberalism, the 'Two-State' solution is the orthodox policy for Israel and Palestine. But Israelis and Palestinians are interspersed and share many of the same resources making it difficult to create two states. So, this research critiques the aforementioned IR theories which underpin the 'Two-State' solution. The conclusion reached is that there ought to be new thinking on how to resolve the Israel-Palestine issue.
Keywords: Arab-Israeli conflict; Jewish-Arab relations; Nationalism -- Israel; Nationalism -- Palestine; Land settlement -- West Bank; Land settlement -- Gaza Strip; Realism; Liberalism; Palestinian Arabs -- Politics and government -- 20th century; Israel -- Politics and government -- 20th century; Israel -- Foreign relations -- Palestine; Palestine -- Foreign relations -- Israel